PREVENTION OF DISPLACEMENT DURING ARMED CONFLICT UNDER THE ISLAMIC LAW - Yusuph, Ismael Funsho; Abdulazeez, Abdurrozaq Opeyemi; Abdulhamid, Asiawu Belgore (Jurnal Syariah, 2023)
The spate at which armed conflicts occur in different parts of the world is worrisome. It is so disturbing that many of these conflicts are purportedly carried out by extremists to perpetrate criminality in the disguise of jihād thereby giving a negative imputation to Islam. One obvious effect of these conflicts is displacement at its alarming rate. It has thus brought about confusion in the eyes of many advocates of human rights and many experts in the field of humanitarian law on the position of Islamic Law on the prevention of displacement. Upon sampling opinions on the position of Islamic law with respect of the humanitarian affairs of people, this study discovered that many people in the field of humanitarian law do not appreciate that there exists humanitarian law under Islamic law even before the development of humanitarian law under conventional international law. In view of that, this paper sets to clear many of the misconceptions accorded to jihād under Islamic law regarding displacement. This discourse shall demonstrate how displacement is controlled and managed under Islamic law. This will exhibit the approach of Islamic law to humanitarian affairs of people and clear misconceptions that it has no provision for humanitarian affairs because of the existence of jihād that purportedly leads to humanitarian problems across the world.